Finite element analysis on stress/strain in CBGA solder joint with different substrates under thermal cycle. (10th June 2009) - Ping, Yang; Shen, Caijun
In this paper, visco-plastic constitutive Anand equation model was used to investigate the behaviour of SnPb solder. A two-dimensional model was built to simulate the working characteristics of soldered joint structure in CBGA by using finite element method. In the meantime, some different kinds of substrates (for example Al2O3, ALN, SiC, BeO) were selected to investigate the mechanical behaviour such as stress/strain process of the solder under thermal cycle. The results shown the maximum stress and strain occurred at the outermost solder. The maximum stress occurred at lowest temperature and hardly decreased with ramp time. The results of finite element analysis also shown the solder have the minimum stress/strain when choose BeO as substrate.